Analyst of Education Quality Improvement in Humbang Hasundutan Regency through the School Literacy Movement - Pardomuan Manullang; Kristina Juniar Saragih; Ridwan Junaedi Tinambunan; Edward Coco Pardede; Alex Bob (Jurnal Multidisiplin Sahombu, 2025)
This study aims to analyze the role of the School Literacy Movement (Gerakan Literasi Sekolah/GLS) in improving the quality of education in Humbang Hasundutan Regency. The study employs a qualitative descriptive-analytical approach using case studies at primary and junior secondary school levels, supported by descriptive quantitative data in the form of literacy pre-tests and post-tests, observations of the learning process, and school assessment results. The findings indicate that the implementation of GLS significantly improved students’ literacy skills, with an average score increase of 23.65%, particularly in interpreting textual meaning (26.68%) and drawing conclusions (25.68%). The quality of the learning process also improved, as reflected in increases in text-based learning (46.15%), discussion and reflection activities (54.17%), active student participation (44.44%), and learning motivation (42.86%). In terms of learning outcomes, students’ literacy achievement increased by an average of 24.91%, accompanied by a reduction in the proportion of students in the minimum proficiency category from 48% to 29%, as well as an increase in the intermediate and advanced categories. Nevertheless, the implementation of GLS still faces major challenges, including limited literacy resources, teachers’ workload, and weak monitoring systems. These findings demonstrate that GLS makes a tangible contribution to improving the quality of both the learning process and learning outcomes, with its effectiveness being strongly influenced by the quality of implementation and the support of the school ecosystem.